The influence of facebook social interaction on healthy eating behaviour and work productivity / Wong Wen Yin - Wong , Wen Yin (2020)
In the current competitive global environment, one of the core determinants of the business success lies in the foundation to workplace productivity amongst the employees. The rise of social media in the health domain can have it play the role of an alternative channel for the promotion of healthy eating behaviour. Literatures outlined that social interaction on Facebook seems relevant towards the promotion of positive health behaviour(s). However, details pertaining to the interaction and its subsequent impact on health remains unexplored. This research examines the influence of Facebook social interaction on healthy eating behaviour and its subsequent impact on work productivity. Using the quantitative research approach, data were collected using self-administered questionnaires. The questionnaires were distributed to working adults online who used Facebook, while its paper counterparts were distributed via snowball, purposive, and convenient sampling. A total of 770 usable responses were collected within 8 months. The structural equation model (SEM) technique was used to assess the proposed research framework. All seven hypotheses proposed in this research were accepted. Both social ties and Facebook use were found to have a positive influence on social interaction on Facebook. The results indicated that social interaction on Facebook plays a significant role in improving healthy eating knowledge, leading towards more positive healthy eating attitude, which in turn results in healthy eating behaviour and increased work productivity. This research pioneered the understanding of the role of Facebook for healthy eating behaviour and work productivity. It integrated two theories, namely social capital theory and consumer socialisation theory for the construction of a comprehensive theoretical framework, which describe the determinants and influence of Facebook social interaction on individuals’ healthy eating attitude, knowledge and behaviour, leading to increased work productivity. The theoretical contribution of this research lies in its extension and verification of social capital theory and consumer socialization theory in online settings, especially in the context of social media. Social ties and Facebook use are introduced as the new antecedents to the existing consumer socialization framework. The findings from this research provide an imminent foundation for organizations when formulating strategies for workplace healthy eating promotion for enhancing work productivity. Facebook can be used to as an effective tool and platform to reach and communicate with the employees about healthy eating. This research confirmed that Facebook could help organizations reach their employees for cultivating healthy eating behaviour and increase work productivity. This research is noteworthy in its contribution towards the advancement of the discipline of health behaviour and productivity management with the application of social media.